(untitled) (CIPEEX, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a neurological condition characterized by alterations in communication, social interaction, and behavior, including repetitive actions and restricted interests. Pharmaceutical care is essential in the care of patients with ASD, ensuring monitoring, medication safety, and therapeutic adherence. Objective: To review the literature on the importance of pharmaceutical care in children with ASD, highlighting the role of pharmacists and caregivers in the rational use of medications and prevention of adverse effects. Method: This is a narrative literature review based on scientific articles. Historical studies, diagnoses, epidemiological prevalence, and clinical characteristics of ASD were analyzed. The PICO strategy and Boolean operators (AND, OR) were used to combine the descriptors "pharmaceutical care," "autism spectrum disorder," and "medication." Results: Pharmacotherapy is common in children with ASD, with 73% using some medication. However, few receive adequate pharmaceutical follow-up, compromising treatment efficacy. Pharmaceutical monitoring allows for dose adjustments, prevention of drug interactions, and guidance for caregivers, improving therapeutic adherence. Medications do not cure ASD, but they control symptoms and promote quality of life and social integration. Conclusion: Pharmacists are essential in the management of ASD, promoting medication safety, therapeutic adherence, and comprehensive care. Their intervention helps reduce risks, guide caregivers, and strengthen clinical pharmacy as part of health policies, improving patients’ quality of life.